Influence of Emotions on The Risk Sensitivity: An Antenarrative Analysis of The Risk Language of a Collapsed Firm - Gurbuz, Elif (2018)
This study explores the reasons why risk management process fails to deliver the expected benefits to the organisations. It investigates the impact of human factor on risk management effectiveness by analysing the effects of the emotions on risk sensitivity at the corporate level. Although there are increasing number of studies on risk perceptions, there are no researches in the risk literature using a technique or methodology to recognise the emotions at the organisational level. This study focuses on a critical failure case and analyses the risk language of a collapsed company by applying an antenarrative approach. It shows how emotions can influence the risk sensitivity and risk attitude in the organisations. Risk management has naturally fearful considerations and perceiving a risk triggers negative emotions. Existing research on individual emotions suggests that although positive emotions influence the risk perceptions, negative emotions play the most important role. However, this study shows that this is not necessarily the case. Positive emotions can negate the negative ones and lead to low risk sensitivity. This study also shows the importance of emotional literacy in order to understand and adjust the risk attitudes to make better decisions.